Assessing Neurocognition via Gamified Experimental Logic: A Novel Approach to Simultaneous Acquisition of Multiple ERPs - Nair, Ajay K.; Sasidharan, Arun; John, John P.; Mehrotra, Seema; Kutty, Bindu M. (Frontiers in Neuroscience, 2016)
The present study describes the development of a neurocognitive paradigm: ‘Assessing Neurocognition via Gamified Experimental Logic’ (ANGEL), for performing the parametric evaluation of multiple neurocognitive functions simultaneously. ANGEL employs an audiovisual sensory motor design for the acquisition of multiple event related potentials (ERPs) - the C1, P50, MMN, N1, N170, P2, N2pc, LRP, P300 and ERN. The ANGEL paradigm allows assessment of ten neurocognitive variables over the course of three ‘game’ levels of increasing complexity ranging from simple passive observation to complex discrimination and response in the presence of multiple distractors. The paradigm allows assessment of several levels of rapid decision making: speeded up response vs response-inhibition; responses to easy vs difficult tasks; responses based on gestalt perception of clear vs ambiguous stimuli; and finally, responses with set shifting during challenging tasks. The paradigm has been tested using 18 healthy participants from both sexes and the possibilities of varied data analyses have been presented in this paper. The ANGEL approach provides an ecologically valid assessment (as compared to existing tools) that quickly yields a very rich dataset and helps to assess multiple ERPs that can be studied extensively to assess cognitive functions in health and disease conditions.